EVALUATION OF THE NEW CONSTRUCTIVE-TECHNOLOGICAL SOLUTION OF THE FENCE STRUCTURE IN THE NON-REMOVABLE FORMWORK (MODERN CONSTRUCTION AND ARCHITECTURE, 2023)
The known constructive and technological solutions of enclosing constructions of buildings in fixed formwork with the use of qualitative, quantitative and general analysis are analyzed. Selected quantitative indicators, such as wall thickness, weight of 1 m2 of wall, heat transfer resistance, area of premises, cost, durability, tendency to shrinkage. Qualitative indicators were used: resistance to the sun, mold, fertilization and destruction, features of delivery of building materials.The method of multicriteria analysis is used to evaluate new structural and technological solutions of fencing structures and determine the most effective technologies. Categories of various constructive-technological decisions in a fixed timbering on the basis of economic consideration of modeling are considered.Such modern constructive-technological decisions of enclosing constructions in a fixed timbering are selected for comparison, as: expanded polystyrene blocks; blocks with wall alignment system; polystyrene concrete blocks; concrete blocks; blocks of cement-chip material; large panels made of expanded polystyrene; three-layer reinforced expanded polystyrene panels; cement particle boards; concrete slabs; frame-monolithic formwork with cement-chipboard cladding; frame-monolithic formwork with cladding of glass-magnesium plates and technology according to the patent UA 149402.The new design and technological solution, which has been developed and patented, is a combination of modern materials that are of great interest and demand to consumers, such as light steel thin-walled structures and expanded polystyrene concrete.The evaluation of technological solutions by quantitative criteria on a ten-point scale, where the minimum and maximum values are assigned points 1 and 10, respectively. Graphical modeling of the summary variants, which are equalized, is performed, and the corresponding diagrams are constructed.
Keywords: structural and technological solutions; enclosing structures; multicriteria analysis; non-removable formwork.